Baseline characteristics of patients with acute ischaemic stroke included in the randomised controlled Find-AF 2 trial - Katrin Wasser; Tobias Uhe; Wolf-Rüdiger Schäbitz; Martin Köhrmann; Martin Dichgans; Johannes Brachmann; Ulrich Laufs; Götz Gelbrich; David Petroff; Christiane Prettin; Dominik Michalski; Johann Pelz; et al. (Neurological Research and Practice)
Abstract Background In the Find-AF 2 randomised controlled trial, we investigate whether a risk-adapted intensified heart rhythm monitoring with subsequent initiation of oral anticoagulation in ischaemic stroke patients leads to a reduction of recurrent ischaemic stroke and systemic embolism. The objective of this analysis is to present baseline characteristics of the overall Find-AF 2 study population and stratified by low or high risk for developing AF. Methods The Find-AF 2 trial included acute ischaemic stroke patients ≥ 60 years of age within 30 days of ischaemic stroke of any cause. Before randomisation, patients received a 24-h Holter-ECG to exclude those with easily detectable AF and to determine the presence or absence of enhanced supraventricular ectopic activity (ESVEA), used as a marker indicating high or low risk for developing AF. Those without AF were randomly assigned 1:1 to either usual care diagnostics for AF detection (control group) or enhanced, prolonged and intensified ECG monitoring (intervention group). In the intervention group, patients with ESVEA received an implantable cardiac monitor (ICM), whereas those without ESVEA received repeated annual 7-day Holter ECGs. We present baseline characteristics of the overall Find-AF 2 population and stratified by ESVEA. Results Between July 2020 and July 2024, 5227 patients (mean age 72.3 ± 7.5 years, 40% female, 2618 intervention group, 2609 control group) were randomised from 52 study centres in Germany within a median of 5 (IQR 3–7) days after the index stroke. The most frequent stroke aetiologies were cryptogenic (60%) and small vessel occlusion (19%). 1152 (22%) patients were at high risk for developing AF and 4075 (78%) at low risk. Patients within the high-risk stratum were significantly older (mean age 75.2 versus 71.5 years, p < 0.001), more often had moderate to severe stroke (34% versus 30%, p < 0.001), non-lacunar (70% versus 64%, p < 0.001) and of cryptogenic aetiology (64% vs 58%, p < 0.001). Conclusions The Find-AF 2 trial has successfully completed recruitment of a large acute ischaemic stroke population with different stroke subtypes. The follow-up is ongoing and results are expected within two years. Trial registration ClinicalTrials.gov, Identifier NCT04371055, registered 24 April 2020.